Recent advances and applications of novel advanced materials in solid-phase microextraction for natural products - Jin, Huang-Fei; Shi, Ying; Cao, Jun (TrAC, Trends in analytical chemistry (Regular ed.), 2024)
Natural products exhibit various biological activities that play essential roles in human health and disease treatment. However, during the quality control of natural products, contamination from toxic components can occur. Consequently, it is worthwhile to discuss efficient and safe methods for extracting active components and separating toxic components from natural products. Currently, solid-phase microextraction technology is the focus of sample preparation methods. This includes solid-phase microextraction, matrix solid-phase dispersion microextraction, dispersive micro solid-phase extraction, and miniaturized solid-phase extraction. Solid-phase adsorbents have been continuously improved to better extract analytes and eliminate matrix interference. This review provides a systematic overview of the applications for the extraction and separation of active and toxic components in natural products from 2018 to 2023 using various extractants (molecularly imprinted polymers, metal–organic frameworks, carbon nanotubes, graphene, graphene oxide, inorganic nanoparticles, activated carbon, and others) in solid-phase type microextraction. Finally, the prospects and future trends are summarized. [Display omitted] •Recent advances in novel absorbents for solid-phase microextraction are summarized.•Active components include flavonoids, alkaloids, saponins, and terpenoids.•Toxic components include pesticides, heavy metal ions, and mycotoxins.•SPME, MSPDME, D-μ-SPE and mini-SPE techniques are briefly introduced.•A discussion on the future trends of solid adsorbents is provided.